2009
DOI: 10.1002/uog.7314
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial blood flow is impaired in women with polycystic ovarian syndrome who are clinically hyperandrogenic

Abstract: Objectives To quantify endometrial and subendometrial blood flow in Caucasian women with polycystic ovarian syndrome (PCOS) (VI: 0.57% vs. 1.11% and 0.86%, respectively, both P = 0.01; VFI: 0.14 vs. 0.42 and 0.28, respectively, both P = 0.02) and subendometrial (VI: 1.59% vs. 3.17% and 2.47%, P = 0.01 and 0.02, respectively; VFI: 0.50 vs. 1.67 and 0.96, P = 0.01 and 0.02, respectively)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…14 Pathologic uterine blood flow in PCOS cases caused reduced endometrial receptivity, therefore increased chances of abortion. Accordingly, in PCOS patients, role of certain medication is more important.…”
Section: Discussionmentioning
confidence: 99%
“…14 Pathologic uterine blood flow in PCOS cases caused reduced endometrial receptivity, therefore increased chances of abortion. Accordingly, in PCOS patients, role of certain medication is more important.…”
Section: Discussionmentioning
confidence: 99%
“…This was in agreement with other studies that reported impaired uterine perfusion with elevated impedance to the uterine arterial blood flow in women with PCOS, as well as in women with unexplained infertility and unexplained recurrent pregnancy loss. [20][21][22][23] Metformin has been introduced as a therapeutic option for PCOS, targeting reproductive and cardiometabolic abnormalities on the basis of its action in reduction of glucose levels and attenuation of insulin resistance, as well as its molecular mechanism involving the liver, the muscles, the endothelium, and the ovary. 24 Jakubowicz and coworkers 25 noted that insulin reduction with metformin increases follicularand luteal-phase serum glycodelin and IGFBP-1 concentrations and enhances luteal-phase uterine vascularity and blood flow in PCOS women as demonstrated by a 20% reduction in vascular resistance in spiral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, ET-1 is expressed in human endometrium and inversely related to plasma estradiol levels, 19 suggesting that ET-1 and estradiol could operate in concert, modulating endometrial blood flow. It is possible that metformin acts on uterine perfusion by reducing androgen levels 23,30 and thus their vasoconstrictive effect on vascular tissues. 22 Furthermore, metformin administration improves endothelial function in women with PCOS as it improves markers of endothelial activation and coagulation, eg, soluble intercellular adhesion molecule, plasma plasminogen activator inhibitor-1, soluble vascular adhesion molecule, plasma endothelin-1, and E-selectin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several conditions in women with recurrent pregnancy loss include high level of serum LH and free testosterone, low luteal progesterone and delayed endometrial development, which are also seen in women with PCOS . Endometrial blood flow was reported to be impaired in hyperandrogenic women with PCOS . In view of these reports, LOD may improve the endometrial development and the subsequent pregnancy outcome after FET by reducing serum androgen level.…”
Section: Discussionmentioning
confidence: 99%
“…12 Endometrial blood flow was reported to be impaired in hyperandrogenic women with PCOS. 13 In view of these reports, LOD may improve the endometrial development and the subsequent pregnancy outcome after FET by reducing serum androgen level. In this case, oocyte retrieval, LOD and chromotubation were performed by LESS.…”
Section: Discussionmentioning
confidence: 99%